An audit of the results of a triplet metronomic chemotherapy regimen incorporating a tyrosine kinase inhibitor in recurrent/metastatic head and neck cancers patients - Vijay M Patil; Santam Chakraborty; T K Jithin; T P Sajith Babu; Satheesh Babu; Shiva Kumar; M S Biji; Atanu Bhattacharjee; Satheesan Balasubramanian (South Asian Journal of Cancer, 2016)
Background: Addition of erlotinib to metronomic chemotherapy (MCT) may lead to further improvement in progression-free survival (PFS) and overall survival in head and neck cancers. The aim of this study was to study the PFS with MCT + erlotinib combination in our setting. Methods: A single-arm prospective observational study conducted at Malabar Cancer Center. Patients warranting palliative chemotherapy for head and neck cancers, having adequate organ function, not-affording cetuximab and not willing for intravenous chemotherapy were included in this study. Oral methotrexate (15 mg/m 2 /week), oral celecoxib (200 mg twice daily), and erlotinib (150 mg once daily) were administered till the progression of the disease or till intolerable side-effects. Patients underwent toxicity (CTCAE version 4.02) and response (RECIST version 1.1) assessment every 30 days. Statistical analysis was performed using SPSS version 16 (IBM, New York, USA). Descriptive statistics and Kaplan-Meier analysis have been performed. Results: A total of 15 patients received MCT. The median age of these patients was 65 years (range: 48-80). The Eastern Cooperative Oncology Group Performance Status was 0-1 in seven patients (46.7%), while it was 2 in eight patients (53.3%). The primary sites of tumor were predominantly oral cavity, 11 (73.4%). Prior to MCT, treatment with palliative radiation therapy was given in 11 patients and curative treatment in two patients. The best response post-MCT was complete remission in two patients, partial remission in seven patients, stable disease in four patients, and progressive disease in two patients. The median estimated PFS was 148 days (95% confidence interval 95.47-200.52 days). For a median follow-up of 181 days, there were only three deaths. Grade 3-4 toxicity was seen in six patients (40%). Dose reduction was required in four patients (26.7%). Conclusion: The addition of erlotinib to an MCT schedule of methotrexate and celecoxib resulted in a promising PFS and should be tested in future studies.